Relationships Between Texture and Rheological Properties in Blanched Apple Slices (var. Granny Smith) Studied by Partial Least Squares Regression - Garcia Loredo, Analia Belen (2014)
The effect of steam blanching (90 or 150 s) on linear viscoelastic and compression properties, sensory texture, and micro- and ultrastructure of cut apple was analyzed. All apple samples showed a solid behavior (storage modulus G′ > loss modulus G″) dominating the viscoelastic response, but both dynamic modules were reduced due to processing. For blanched tissues, the instantaneous elastic compliance J0 and the retarded compliances J1 and J2 increased and the steady-state viscosity decreased. Values of mechanical parameters and texture attributes (except cohesiveness) decreased for blanched tissues. Partial least squares regression analysis (PLS) technique was used to study how texture characteristics (dependent variables) were related to rheological properties (independent variables) of untreated and blanched apples. Sensory hardness and crispness were negatively related to J0, J1, and J2 and positively correlated to G′ at intermediate and high frequencies (ω) and G″ at low frequencies. Sensory fracturability was positively correlated with G′ at ω = 0.1 1/s and G″ at ω = 100 1/s. Juiciness and sensory fracturability were positively correlated to instrumental hardness and area 1, and crispness and sensory hardness were positively related to instrumental fracturability. Structure differences (rupture of membranes, decrease in cell-to-cell contact, degradation of cell walls, changes in microfibril arrangements) could explain some changes observed in rheological properties and texture of blanched apples.